Acute effect of aerobic and resistance exercises on cardiovascular and neuromuscular responses in normotensive - Ruiz, Roberto José; Pires, Paulo Fernandes; Pelai, Elisa Bizetti; Castro, Ester Moreira de; Mescollotto, Fabiana Foltran; Moreno, Marlene Aparecida; Bigaton, Delaine Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Introduction: the literature report the effect of different types of exercise (aerobic and resisted) on cardiovascular and neuromuscular behavior after exercise. Objective: the objective of this study was to verify the acute effect after a resisted or aerobic exercise session on arterial pressure (BP), heart rate (HR), muscular strength and electromyography (EMG) activity of the rectus femoris (RF), vastus lateralis (VL) and vastus medialis (MV) in normotensive individuals. Method: the study included eight men (27.3 ± 3.1 years, 76.4 ± 9.7 kg, 1.80 ± 0.10 m, 24.3 ± 1.6 kg/m2 ), physically active individuals who randomly performed an aerobic exercise session (treadmill, 30 min, 60-70% of the reserve heart rate), or a resisted exercise session (nine exercises, three sets, 70% 1RM, 8 -12 repetitions). The BP, HR, EMG and muscle strength, were analyzed at rest before exercise and for 60 min after exercise. Results: as a result, systolic BP after the exercises (aerobic and resisted) remained lower than the pre-exercise rest values, with 30, 45 and 60 min (p<0.05) of recovery. On the other hand, the diastolic BP was lower after resistive exercise in all periods of recovery (p <0.01) in relation to pre-exercise. HR values remained elevated after aerobic and resisted exercise, in all recovery periods (p <0.05). Muscle strength and electromyography activity did not show significant differences after exercise. Conclusion: independently of the exercise type, occurs post-exercise hypotension (PEH), increase the HR during the recovery period and reestablishment of muscle strength and myoelectric activity of muscles compared to pre-exercise.